E-commerce perspectivas para o avanço no comércio mossoroense - Melo Neto, Pedro Mendes de (Universidade Federal Rural do Semi-Árido, 2019)
The media is present in the daily life of the whole society and the market is taking advantage of this medium to advertise services. In Mossoró/RN the situation is not different. The owners of establishments are searching for tools, in order to manage to increase your number of clients and, consequently, the number of sales. This research, conducted in the trading of Mossoró/RN, aims to demonstrate the technological advances in the local market, from the use of social networking and how marketers are taking advantage of them in your endeavors to innovate and attract new clients. To perform this research noted that there are still obstacles that must be overcome, as improvement, training and among others. After exceeding this barrier, the owners have managed to improve their incomes
Artigo Acadêmico
Keywords: Inovação tecnológica; Comércio eletrônico; Redes sociais; Technological innovation; Electronic commerce; Social networks; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA